The legal understanding of slavery from the historical to the contemporary - Allain, Jean, 1965- (Oxford : Oxford University Press, 2013)
This title examines how slavery is understood in law, showing how the legal definition of slavery has evolved and continues to be contentious. It traces the understanding of slavery from Roman law through the Middle Ages, the 18th and 19th centuries up to the modern day manifestations, including forced labour and trafficking in persons.
Description based on online resource; title from PDF title page (viewed on Oct. 31, 2012).
Keywords: Slavery -- Law and legislation; Slavery -- Law and legislation -- History